Red Blood Cell Distribution Width Predicts Pulmonary Hypertension Secondary to Chronic Obstructive Pulmonary Disease - Jie Yang; Chuanmei Liu; Lingling Li; Xiongwen Tu; Zhiwei Lu (Canadian Respiratory Journal)
Purpose. This study aims at investigating the predictive value of red blood cell distribution width (RDW) in pulmonary hypertension (PH) secondary to chronic obstructive pulmonary disease (COPD). Methods. 213 eligible in-hospital COPD patients were reviewed between May 2016 and May 2018, including 39 cases with PH and 174 without PH. Clinical data including demographic characteristics, comorbidities, and results of ultrasound scans, imaging examinations, and laboratory tests were recorded. Results. Increased RDW level was observed in COPD patients with PH compared with COPD patients without PH, with 15.10 ± 1.72% versus 13.70 ± 1.03%, respectively (p<0.001). RDW shared positive relationships with brain natriuretic peptide (BNP) (p=0.001, r = 0.513), pulmonary artery (PA) systolic pressure (p=0.014, r = 0.390), and PA-to-ascending aorta (A) ratio (PA : A) (p=0.001, r = 0.502). Multivariate analysis indicated that RDW, BNP, and PA : A > 1 were the independent risk factors of PH secondary to COPD (p<0.05). The AUC of the RDW in patients with PH was 0.749 ± 0.054 (p<0.001). The optimal cutoff value of RDW for predicting PH was 14.65, with a sensitivity and a specificity value of 69.2% and 82.8%, respectively. Conclusion. RDW is significantly increased in COPD patients with PH and thus may be a useful biomarker for PH secondary to COPD.